An Meningkatkan Keterampilan Berpikir Kreatif Siswa Menggunakan Lembar Kerja Berbasis STEM-PjBL - Sekar Tria Mulyaningrum; Noor Fadiawati; Kartini Herlina (Postgraduate, University of Mataram, 2025)
This study aims to determine the characteristics, teacher and student responses, and the effectiveness of STEM-PjBL-based LKS on the material of making peuyeum to improve creative thinking skills in the developed biotechnology material. The method used is a mixed method with an embedded experimental model. This study involved 10 biology teachers and 20 students in Lampung Province at the pre-intervention stage and after the intervention involving 32 grade X students of SMA Negeri 3 Bandar Lampung and 2 teachers as research observers and 1 teacher as a teacher. Data collection was carried out through a LKS validation questionnaire on the aspects of material suitability, construction, and readability for experts, a teacher response questionnaire covering material suitability and readability, and a student response questionnaire after implementing learning using STEM-PjBL-based LKS, as well as a set of pretest-posttest instruments for creative thinking skills. The data analysis technique in this study used the paired sample t-test. The average percentage of expert validation results for the material suitability aspect was 89.77%, construction 90.62%, and readability 87.50% so that the STEM-PjBL-based peuyeum making worksheet was declared valid and had a “very high” criterion according to Arikunto's assessment standards with characteristics following the STEM-PjBL syntax and containing local wisdom in the form of peuyeum. The teacher's response to the material suitability aspect was 93.18% and readability 91.66% and the average student response was 84.81% so that the worksheet was suitable for use in biology learning with a